Allegories of Contamination : Pier Paolo Pasolini's Trilogy of Life. - Rumble, Patrick (Toronto Italian studies., 2015)
Rumble offers a comparative study based on the concept of 'aesthetic contamination, ' which is fundamental to the understanding of Pasolini's poetics.